Numerical simulation of the elastic behavior of reinforced concrete slabs up to first cracking using rigid body-spring discrete element method - Garde, Felix V. Jr.; Tingatinga, Eric Augustus J. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The behavior of reinforced concrete (RC) slabs under loads well below service level may be assumed linear elastic. Elastic plate analysis can be applied, however, closed form solutions are only available to slabs with typical geometry, loads and support conditions. When subjected to different types of loading combinations, boundary conditions and having geometric irregularities, analytical solution could not be easily done. This study presents a numerical model to predict the capacities and failure patterns of RC slabs using Rigid Body-Spring Discrete Element Method. The proposed slab model composed of rigid plate elements and flexural or rotational springs is based on the yield line theory which assumes that the nonlinear behavior of the RC slab subjected to transverse loads is contained in plastic or yield lines. In this model, the displacement of the slab is completely described by the rigid elements and the deformation energy is concentrated in the flexural springs uniformly distributed at the potential yield lines. The calculation of spring parameters is based on Euler-Bernoulli beam theory and expressed as a function of flexural rigidity and mesh geometry. Three different available experimental slab models representing various geometrics, reinforcements, loadings and support boundary conditions were used to validate the model by comparing the computed cracking loads with the reported experimental results. Results show that for a corner-supported square slab subjected to central point load, a difference of 5.0% was obtained. For simply supported square and rectangular slabs subjected to uniform transverse load, a difference of 1.31% and 0.77%, respectively, were observed. This good agreement in the results presents a practical advantage of the method that may be used to investigate nonlinear behavior of RC slabs.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete slabs -- Testing